Peradilan Agama Islam di Negara Syiah: Republik Islam Iran Pasca Revolusi - Rahmawati; Asasriwarni; Zulfan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Ayatollah Imam Khomeini became an important figure in the independence of the Islamic Republic of Iran as a Shia state, using Wilayat al-Faqih as its legal concept with the Imamate principle. The principle of Imamate explains that as long as the Twelfth Imam (Imam Mahdi) is still unseen, the government is led by an Imam whose qualifications are close to the Imam in terms of knowledge and spirituality. Consequently, the way the law is administered and the way the law is adjudicated in the State of Iran is up to the Wali Faqih, and when the Wali Faqih agrees, the rules can be implemented. This paper aims to examine the history, legal system, and judiciary of the Islamic Republic of Iran. The research data is obtained from literature studies (library research) and is descriptive and analytical. The result of the discussion is that Iran has gone through a long history starting from the first Persian empire, namely Akhameniyah, to the occurrence of post-Revolution until now. Iran is a country that adheres to Shi'a Islam and uses the legal concept of Wilayat al-Faqih where high power is in the hands of Wali Faqih. The judicial council is the holder of judicial power, whose head of the judiciary is directly elected by the Wali Faqih. Some of the courts in Iran include the Revolutionary Court, the General Court, and the Supreme Court of Cassation. In Iran, there is also a Clerical Court/SCC that tries clerics or Muslim scholars and this court is very secretive